Streamlined Synthesis and Evaluation of Teichoic Acid Fragments. Issue 16 (19th February 2018) - van der Es, Daan; Berni, Francesca; Hogendorf, Wouter F. J.; Meeuwenoord, Nico; Laverde, Diana; van Diepen, Angela; Overkleeft, Herman S.; Filippov, Dmitri V.; Hokke, Cornelis H.; Huebner, Johannes; van der Marel, Gijsbert A.; Codée, Jeroen D. C.
Abstract: Teichoic acids (TAs) are key components of the Gram‐positive bacterial cell wall that are composed of alditol phosphate repeating units, decorated with alanine or carbohydrate appendages. Because of their microhetereogeneity, pure well‐defined TAs for biological or immunological evaluation cannot be obtained from natural sources. We present here a streamlined automated solid‐phase synthesis approach for the rapid generation of well‐defined glycosylated, glycerol‐based TA oligomers. Building on the use of a "universal" linker system and fluorous tag purification strategy, a library of glycerolphosphate pentadecamers, decorated with various carbohydrate appendages, is generated. These are used to create a structurally diverse TA‐microarray, which is used to reveal, for the first time, the binding preferences of anti‐LTA (lipoteichoic acids) antibodies at the molecular level. Abstract : Using a streamlined, automated solid‐phase synthetic approach, well‐defined glycosylated, glycerol‐based teichoic acid oligomers were synthesized. These are used to create a structurally diverse teichoic acid microarray, which is used to reveal, for the first time, the binding preferences of anti‐LTA antibodies at the molecular level.